Vaikų užklasinio skaitymo padėties ir turinio bruožai 1919–1940 metų laikotarpiu - Raguotienė, Genovaitė (Knygotyra, 1970)
The article treats of the problem of pupils’ out-of-curriculum reading in Lithuanian schools under the rule of bourgeois governement. It deals with the content and the main tendencies of that reading. The analysis of the questions concerned is based upon the data taken from the press of those times and archives. The author of the article shows the ideological and political struggle which took place in Lithuanian society of that time when discussing the aforesaid problem. The progressive-minded teachers, librarians and other intellectuals did much for the improvement of pupils’ reading mater. Fighting against the reactionary course of the ruling class they solved many questions of that reading. Working under difficult and complicated circumstances they cultivated childrens’ interest for books, took care of, and struggled for, democratic character of pupils’ reading. The author points out the democratic traditions of Lithuanian teachers and librarians when treating the problem of pupils’ out-of-curriculum reading.